Integration of in silico and in vitro approaches to evaluate antioxidant and anticancer properties of Tribulus terrestris extracts - Muhammad Hussnain Siddique; Rahat Andleeb; Asma Ashraf; Muhammad Zubair; M. Fakhar-e-Alam; Sumreen Hayat; Saima Muzammil; M. Atif; Sulman Shafeeq; Muhammad Afzal (Arabian Journal of Chemistry, 2022)
Plants have been found useful in treating many human diseases caused by bacteria and viruses. The ability to synthesize compounds by plant secondary metabolism makes them an invaluable source of pharmaceutical and therapeutic products. The present study was designed to evaluate the phytochemical constituents, antioxidant, and anticancer activities of Tribulus terrestris seed extracts on HepG2 cell lines. TPC and TFC contents were 51 ± 0.7 mg GAE/g and 66.5 ± 0.4 mg QE/g, respectively. The antioxidant profile of the T. terrestris revealed that all the extracts have antioxidant potential and display the highest antiradical behavior in the pattern of methanolic > acetonic > chloroform > n-hexane, through DPPH, FRAP, OH radical scavenging, and NO radical scavenging assays. The antioxidant activity explored at the cellular level against H2O2-induced DNA damage showed a dose-dependent antioxidant effect of T. terrestris. Moreover, the methanolic extracts of all plant extracts showed notable thrombolytic potentials, the percentage of clot lysis accounted for T. terrestris was 33%, 27%, 17%, and 6% which indicated the significant clot lysis of methanolic and acetonic extracts in contrast to positive and negative standards. The genotoxicity was assessed through comet assay which exposed that T. terrestris at a low dose (0.5 mg/mL) is considered to be safe for effective treatment. MTT assay using HepG2 cell lines revealed that the highest tested concentration i.e., 100 μg/mL of the methanolic extract resulted in 86% cell viability compared to the control group. In silico study, from 14 selected compounds, three compounds, Heptacosane, Apiol, and Palmitic acid showed an affinity with target protein 51X0. The present findings may serve as a guideline for the standardization and validation of natural drugs containing the T. terrestris as an ingredient.